(untitled) (Research, Society and Development, 2021)
Introduction: The nurse has an extremely important role in the postpartum period, being able to approach and assist in the construction of the maternal-infant bond, through their assistance also aiming at the health of both. However, good care practices during labor and birth are essential. Objectives: The general objective of the research is to identify the interventions performed by nursing during the hospitalization of newborns. As specific objectives, there is an interest in showing the bond that can be created between the nursing team and the NB’s family. Methodology: Articles were tabulated by title, authors, year of publication, journal, objectives, results and conclusion. From then on, bibliometric analysis began, which were grouped by similarity in the form of categories. Results and discussions: It was possible to notice common and divergent points, having more direct and precise information that helped them during the elaboration of this work. Conclusion: The assistance of the hospital staff must work to ensure continuous care and adequate form so that there is no risk to the newborn or the mother. Since all the service provided after the birth of the NB favors a good adaptation to something that is new for both the baby and the mother.